Vectorial Transmission of Malaria in Major Districts of Côte d'Ivoire. Issue 3 (30th November 2019) - Assouho, Konan F; Adja, Akré M; Guindo-Coulibaly, Négnorogo; Tia, Emmanuel; Kouadio, Affoué M N; Zoh, Dounin D; Koné, Moussa; Kessé, Nestor; Koffi, Bernard; Sagna, André B; Poinsignon, Anne; Yapi, Ahoua
Abstract: To better understand the influence of periodic mass distribution of Long-Lasting Insecticidal Nets (LLINs) on malaria transmission, a 1-yr entomological survey was conducted in three major districts of Côte d'Ivoire. Mosquitoes were sampled by Human Landing Catches (HLC) in urban and rural areas of San Pedro and Abidjan (coastal), and in Yamoussoukro (central). Mosquitoes were identified morphologically and by molecular methods. The Plasmodium falciparum circumsporozoite (CSP) indices were measured by ELISA, and the Entomological Inoculation Rates (EIR) were calculated for each species and area. Anopheles gambiae s.l. Giles (Diptera: Culicidae) and Anopheles nili Theobald (Diptera: Culicidae) were identified in coastal districts, while An. gambiae s.l. and Anopheles funestus Giles (Diptera: Culicidae) were reported in the central district. In urban areas, malaria vectors showed a low aggressiveness (<10 bites per person per night), except in Yamoussoukro, where up to 18.9 b/p/n were recorded. The annual EIR was higher in the central urban area (138.7 infected bites per person per year) than in coastal ones (10–62 ib/p/n). In rural areas, malaria vectors were highly aggressive with an average 13 b/p/n for An. gambiae s.l, 21.2 b/p/n for An. nili and 12 b/p/n for An. funestus . The annual EIR ranged between 94.9 and 193.4 infected bites per person per year. This work indicates that, despite repeated mass distribution of LLINs, malaria transmission remains high and heterogeneous across Côte d'Ivoire. Malaria transmission was lower in coastal urban areas than in the central one, and remains high rural areas where two additional Anopheles vectors are involved in malaria transmission.